Discriminant power in game-related statistics and game result according to setter position in the 2010 World Volleyball Championship - Joao, P. V.; Silva, M.; Lacerda, D.; Vaz, L. (World Congress of Performance Analysis of Sport IX, 2012)
The study of the knowledge of the match is not a recent concern, since one of the biggest challenges of the investigation has been, for a long time, the concern for the interpretation and understanding of the development of the specific knowledge in team sports. The aim of the present study intends to identify the actions of the game which discriminate the result (win/lose), according setter location (attack zone and defense zone). The sample of this study has been taken from the World Championship of Volleyball Male Seniors . Italy 2010. We analyzed n=24 games, which outcomes the result of 90 sets played throughout the 3rd round, which are the elite matches until the present study. These correspond to 24670 actions, in which 4083 services, 3434 receptions, 4906 attacks (3030 attacks after reception, 1876 attacks in transition), 2109 blocks, 1933 digs and 3299 sets. The Data Volley software was used in this research. Were analyzed the discriminating function (AD) in order to identify, throughout canonical structuring coefficient (CCE), the indicators which contribute the most to establish the maximum difference between the victories and defeats. We consider as relevant to the interpretation of the linear composite the |CCE| . 0,30 (Tabachnick & Fidell, 1996). The level of significance was established in 5%. The calculation of the results was made by the software SPSS version 17.0. Regarding the results obtained throughout the positioning of the setter (defense zone and attack zone), the discriminating variables were service point, service error, excellent pass, pass error, excellent defense, side out error, counter attack point, attack point, excellent reception, side out point and reception error. The service point action, they have a probable associate to the success (win). It is very important training the efficacy of this action according the final outcome. The teams with less error in defense and block movements end up having the most successful result. Outcome, the pass has particular importance in the final outcome of the match when the setter is in offensive zone; the service point is rather important in the victory when the setter is in offensive zone. The counter attack discriminates the final outcome when the setter is in defensive zone; and finally the quality of the reception is determinant regarding the final outcome, when the setter is in defensive zone.